Comparison of an AC‐taxane versus AC‐free regimen and paclitaxel versus docetaxel in patients with lymph node‐positive breast cancer: Final results of the National Surgical Adjuvant Study of Breast Cancer 02 trial, a randomized comparative phase 3 study. Issue 5 (12th January 2017) - Watanabe, Toru; Kuranami, Masaru; Inoue, Kenichi; Masuda, Norikazu; Aogi, Kenjiro; Ohno, Shinji; Iwata, Hiroji; Mukai, Hirofumi; Uemura, Yukari; Ohashi, Yasuo
Abstract : BACKGROUND: In postoperative patients with breast cancer, the combination of an anthracycline and cyclophosphamide (AC) followed by a taxane is a standard regimen. In the current study, the authors examined whether AC could be safely omitted, and compared the effectiveness of paclitaxel versus docetaxel. METHODS: Female postoperative patients with axillary lymph node‐positive breast cancer were eligible for enrollment in this phase 3, open‐label, randomized controlled trial at 84 centers in Japan. Patients were randomized to 4 cycles of doxorubicin at a dose of 60 mg/m 2 and cyclophosphamide at a dose of 600 mg/m 2 (AC) followed by 4 cycles of paclitaxel at a dose of 175 mg/m 2 (ACpT) or AC followed by 4 cycles of docetaxel at a dose of 75 mg/m 2 (ACdT), or 8 cycles of paclitaxel (PTx) or docetaxel (DTx) every 3 weeks. The primary endpoint was disease‐free survival (DFS). Secondary endpoints included overall survival adverse events. The authors adopted a 2 × 2 factorial design to examine the AC containing‐regimens (ACpT and ACdT) versus the AC free‐regimens (PTx and DTx), and the paclitaxel‐containing regimens (ACpT and PTx) versus the docetaxel‐containing regimens (ACdT and DTx). RESULTS: Of 1060 patients, 1049 were treated and included in the intention‐to‐treat population. The DFS results did not demonstrate noninferiority between the AC‐containing and the AC‐free regimens (hazard ratio [HR], 1.19; 95% confidence interval [95% CI], 0.982‐1.448 [ P noninferiority  = .30]). Better outcomes were noted in patients treated with the docetaxel‐containing regimens compared with the paclitaxel‐containing regimens with respect to DFS (HR, 0.72; 95% CI, 0.589‐0.875 [ P =  .0008]) and overall survival (HR, 0.75; 95% CI, 0.574‐0.980 [ P =  .035]). Neutropenia, nausea, and vomiting were found to occur more often in the AC‐containing arms, whereas the incidence of edema was greater in the docetaxel‐containing treatment arms. CONCLUSIONS: Noninferiority in DFS was not demonstrated between the AC‐containing and AC‐free regimens. Compared with a similar regimen of paclitaxel, docetaxel appeared to increase the DFS. Cancer 2017;123:759–68. © 2016 American Cancer Society . Abstract : In postoperative patients with breast cancer, the combination of an anthracycline and cyclophosphamide followed by a taxane is a standard regimen. The results of the current phase 3 study demonstrate that noninferiority in disease‐free survival is not shown between regimens containing the combination of doxorubicin plus cyclophosphamide and those that do not, and that compared with a similar regimen of paclitaxel, docetaxel increased disease‐free survival.